(untitled) (Tribhuvan University Journal of Microbiology, 2025)
Objectives: The study was conducted to analyze antimicrobial activities of leaf extract of Guava against Gram positive and Gram negative bacteria. Method: The leaf samples of Guava were collected from different parts of Lalitpur district and were processed to analyze the antimicrobial property of different solvent extract of guava leaf by using Agar well diffusion method. Results: The results of the study indicated that three out of three of the crude solvent extract prepared from the leaves of guava, Methanol, Ethanol and Distilled water showed inhibitory activity against bacteria. Only Gram-positive bacteria, Staphylococcus aureus were susceptible to the all the extract, while Escherichia coli did not show any inhibitory action. Among the four sample extract of guava leaf from different solvent, the distilled water showed highest zone of inhibition by 25mm, followed by methanol extract with 20mm zone of inhibition and ethanol extract by 19mm zone of inhibition. At 10mg/50µL, the distilled water extract showed more antimicrobial activity with mean zones of inhibition 23.66mm than Methanol and Ethanol extracts with mean zone of inhibition 18mm and 16.33mm respectively. Conclusion: Leaf extract of Guava showed the antibacterial activity against Staphylococcus aureus.